A Green Lipophilization Reaction of a Natural Antioxidant - Valeria Pappalardo; Nicoletta Ravasio; Ermelinda Falletta; Maria Cristina De Rosa; Federica Zaccheria (MDPI AG, 2023)
A natural antioxidant, widely spread in plants, chlorogenic acid (CGA), can be lipophilized through a heterogeneous, non-enzymatic, catalytic process. Thus, sulfonic resins under no solvent conditions allow to obtain a series of esters in up to 93% yield through reaction of CGA with fatty alcohols of different chain length. The reaction takes place in one single step under mild conditions with conversions up to 96% and selectivity up to 99%. Product recovery in high purity was very easy and the esters obtained were fully characterized with spectroscopic techniques and through the DPPH test to verify the preservation of antioxidant activity. According to this test, all of them showed increased activity with respect to the parent acid and anyway higher than butylated hydroxyanisole. An in-silico method also suggested their very low toxicity. The increased lipophilicity of the esters allows their formulation in cosmetic and nutraceutic lipid-based products.